Communication Pattern Of The Communication Leadership To Staff And Lecturers At Private Higher Education, Banyuwangi District: Study Of Communication Ethnography - Erlangga, Mohammad (International Journal of Educational Research & Social Sciences, 2022)
This study analyzes the communication patterns made by the chancellor to his lecturers and staff in one of the Universities in Banyuwangi district. The purpose of this research is to identify the rector's speech acts in this case the use of speech codes, the choice of language used for code switching and code mixing, and speech events that cover formal and informal situations. The method used in this study is a qualitative method with an ethnographic communication approach. Sources of data in this study are the chancellor, lecturers, and staff. The data in this study were the utterances of the chancellor, lecturers, and staff which were obtained through observation, interview, recording, listening, and recording methods, and were analyzed using an ethnographic study of communication. The results of this study indicate that there are differences in the use of the type of language used by the chancellor to staff, and the chancellor to lecturers. Thus, the findings in this study are the use of different languages ​​and code mixing are influenced by three factors, including cultural factors, speech competence factors, and communicative competence factors. The use of language and code mixing is used to achieve communication goals.